Evaluation of Public Health Interventions in Reducing the Burden of Malaria Infection in Emohua Community, Rivers State, Nigeria. - Okoro, Chinyere Ihuarulam; Azike, Chidimma Anthonia; Nwokah, Easter Godwin; Thompson, Imomoemi Nwinam; Ekesiobi, Ujunwa Sandra; Dokubo, Isaiah Ezinna (British Journal of Healthcare and Medical Research, 2024)
It is assumed that just a few persons are beneficiaries of one or more public health interventions in local communities. The aim of this study was to evaluate public health interventions in reducing the burden of malaria infection in certain communities in Emohua in Rivers State. A cross-sectional community-based study was conducted on the study population. A pre-tested questionnaire was designed to gather information from the participants in the communities. As part of the study design, blood samples were collected with consents from the participants and were examined for the presence of malaria parasites with the use of rapid diagnostic test (RDT) kits. The result obtained from the information gathered from the participants, showed that 98 % of the participants have pre-knowledge (sensitization) of malaria, 15%, 41 % and 44 % said they were sensitized through TV, radio and medical outreach respectively. 40 % admitted having benefitted from public health interventions. From the 40 % who benefited from public interventions, 20 % said they received mosquito nets, 6 % said they received insecticides, 10 % said they received counseling and 4 % said they received malaria drugs. Furthermore, 46 % of the participants said the interventions were effective in the reduction of malaria while 54 % were not certain about the effectiveness of these interventions. Furthermore, the prevalence of malaria was 8%. In conclusion, the distributions of public health interventions across these communities studied were poor. Less than 50 % of the participants have one way or the other benefited from public health malaria interventions. The malaria prevalence may be due to malaria sensitization preventive measures undertaken by the individuals. There is a need for even distribution of public health intervention in Emohua.